Effect of Ferroresonance on Wind Turbine: Comparison of Atp/Emtp and Matlab/Simulink - Ajibola Akinrinde; Andrew Swanson; Remy Tiako (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Different developers have produced several software packages as solutions to model electrical power systems for the purpose of carrying out diverse analyses to solve immediate and unforeseen problems in power systems. In this study, ATP/EMTP and Matlab/Simulink packages were compared in regards to their capability to give accurate results, time of simulation and ease of simulation when modeling DFIG wind turbine. Furthermore, ferroresonance caused by one stuck pole during switching operations were analyzed on both software. Characterization of resulting ferroresonance was done using Fast Fourier Transformation (FFT) analysis, phase plane diagram and Poincaré mapping. Chaotic mode ferroresonance was found in both ferroresonance events. However, ATP could only perform FFT analysis while other analyses were performed on Matlab/Simulink. There are differences in the results obtained from the two packages; overvoltage of 4.22 P.U. and 3.77 P.U. was experienced during opening and closing operation on ATP/EMTP model while 6.36 P.U. and 4.63 P.U. respectively was obtained on Matlab. However, ATP is faster in regards to time of simulation with CPU time of 110.58 secs and simulink simulation time was 130.81 secs. Finally, it was easier to carry out the simulation on Simulink.